Hubungan Panjang Badan Lahir dan Berat Badan Lahir Dengan Terjadinya Stunting Pada Balita Didaerah Lokus dan Non Lokus Stunting Dikabupaten Sidrap - Resky Devi Akib; Syahriani; St. Nurbaya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Stunting is one of the problems that occur in toddlers today. Globally, stunting in children under five reached 165 million in 2011. According to the World Health Organization (WHO) in the Global Nutrition Targets 2025, stunting is an irreversible growth disorder that is influenced by mostly inadequate nutritional intake and is caused by repeated infections for 1000 days. first life. Therefore, it is very important for children aged 0-2 years to ensure optimal nutritional intake. This study aims to determine how the relationship between birth length and birth weight occurs in stunting loci and non locus areas. The purpose of this study was to determine whether there was a relationship between the incidence of birth length and birth weight with the incidence of stunting. This study used a correlation analytic survey method with a cross-sectional time approach. with sampling using total sampling, data analysis using Chi Square. Research results There is a relationship between the incidence of birth length and birth weight with the incidence of stunting in locus and non-locus areas in Sidrap district.